Effect of Solid-to-Gas Ratio on Powder Fuel Mixing in a Cavity-Based Supersonic Combustion Chamber with Induced Shock: A Numerical Study - Zuodong Liang; Ming Jiang; Shaoqing Hu; Kai Ma; Guiyang Xu; Wenjie Wang; Yuezu Miao; Hongyan Li (Aerospace)
The development of powder-fueled ramjets is challenged by the mechanisms of flow mixing for the combustion of powder fuel in supersonic airflows. This paper describes a series of numerical simulations on the injection process of boron powder fuel in a cavity-based supersonic combustion chamber with induced shock. Under different solid-to-gas ratios ranging from 20 to 0.1, this study explored the evolution of supersonic flow fields with strong shear and discontinuities. It also discusses the flow processes and mixing characteristics of powder fuel within them. The study found that the enhancement of powder fuel mixing is mainly related to the rotational regions of large-scale vortex structures. Vortex structures with the required intensity and area can be obtained by adjusting the appropriate solid-to-gas ratio. Moreover, reasonable induction methods can enhance the interaction between particles and vortex structures, thereby achieving mixing enhancement. The interaction between powder fuels and the peripheral rotating regions of these vortices significantly improves the mixing efficiency, with the highest average mixing efficiency increased by 30%. This research lays a foundation for developing mixing enhancement strategies and supports the advancement of efficient and stable powder-fueled ramjets.